GPS analysis of elite level hockey - Jennings, D. (2012)
This thesis investigated the suitability of Global Positioning System (GPS) to assess activity profiles in elite hockey. Study one established validity and reliability of GPS units (1 and 5 Hz) to assess distance during movement`s common to team sport. Measurement accuracy decreased as speed increased in both straight line and change of direction (COD) courses. Difference between criterion and GPS measured distance ranged from 9.0 - 32.4%. Higher sampling rates improved validity regardless of distance and locomotion. Reliability improved as distance travelled increased but decreased as speed increased. Total distance (TD) over the team-sport circuit exhibited the lowest variation (Coefficient of variation (CV) 3.6% at 1 and 5Hz), while sprinting over 10 m demonstrated the highest (CV 77.2% at 1 Hz). Study two examined the variability between GPS units. Differences (±90% CI) between the units ranged from 9.9 ±4.7% - 11.9 ±19.5% for straight line running, 9.5 ±7.2% - 10.7 ±7.9% in COD courses and 11.1 ±4.2% in the team-sport circuit. Similar variability was displayed for TD (10.3 ±6.2%) and High Speed Running Distance (HSR) (10.3 ±15.6) during match play. It is recommended players wear the same GPS unit for each exercise session. Study three compared activity profiles of national and international hockey players. International players covered more TD (13.9%) and HSR (42.0%) than sub-elite players. Less running was performed during the second half in both competitions (TD = 6.1-7.5%). Study four investigated the influence of multiple games on exercise intensity during an international hockey tournament. Two levels of comparison were made; (a) data from subsequent matches were compared to match 1 and (b) data from each match compared to a tournament average (TA). The amount of HSR was maintained as the tournament progressed. When compared to the TA, defenders showed more variation in each match. All positions showed lower movement outputs when the team won by a large margin. It was possible for elite team sport athletes to maintain exercise intensity when playing six matches in a period of nine days.